Effects of Age and Working Memory Load on Syntactic Processing: An Event-Related Potential Study - Alatorre-Cruz, Graciela C.; Silva-Pereyra, Juan; Fernández, Thalía; Rodríguez-Camacho, Mario A.; Castro-Chavira, Susana A.; Sanchez-Lopez, Javier (Frontiers in Human Neuroscience, 2018)
Cognitive changes in aging include working memory (WM) decline, which may hamper language comprehension. An increase in WM demands in older adults would probably provoke a poorer sentence processing performance in this age group. A way to increase the WM load is to separate two lexical units in an agreement relation (i.e., adjective and noun), in a given sentence. To test this hypothesis, event-related potentials (ERPs) were collected from Spanish speakers (30 older adults; mean age = 66.06 years old and 30 young adults (mean age = 25.7 years old) who read sentences to detect grammatical errors. The sentences varied with regard to (1) the gender agreement of the noun and adjective, where the gender of the adjective [feminine] either agreed or disagreed with the noun, and (2) the WM load (i.e., the number of words between the noun and adjective in the sentence). No significant behavioral differences between groups were observed in the accuracy of the response, but older adults showed longer reaction times regardless of WM load condition. Compared with young participants, older adults showed a different pattern of ERP components characterized by smaller amplitudes of LAN, P600a and P600b effects when the WM load was increased. A smaller LAN effect probably reflects greater difficulties in processing the morpho-syntactic features of the sentence, while smaller P600a and P600b effects could be related to difficulties in recovering and mapping all sentence constituents. We concluded that the ERP pattern in older adults showed subtle problems in syntactic processing when the WM load was increased, which was not sufficient to affect response accuracy but was only observed to result in a longer reaction time.